A study on teachers' job satisfaction in a Singapore secondary school - Lai, Serene Soon Hoon (2008)
Job satisfaction, a construct that is both abstract and subjective, is hard to define. Nevertheless, it wields considerable influence in teachers' sense of fulfillment in their work and overall well-being. Studying an issue like this can be problematic.